Pengaruh Konservatisme Akuntansi, Corporate Governance Dan Sales Growth Terhadap Tax Avoidance - Prasasti, Widya Eko; Astuti, Puji; Sugeng, Sugeng (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This study aims to determine the effect of accounting conservatism, corporate governance and sales growth on tax avoidance in food and beverage companies listed on the IDX. Tax Avoidance is an effort to reduce, or even eliminate the tax burden that must be paid by a company, in a manner permitted by existing laws and regulations. The subjects of this study were Food and Beverage Companies listed on the Indonesia Stock Exchange in 2020-2023. This study has 95 populations and uses a purposive sampling method as a way to select samples, so that 19 companies that meet the research criteria are obtained. The data analysis method used is multiple linear analysis using the SPSS version 25 program. Where this multiple linear analysis test uses the normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, coefficient of determination test (R2), F test, and t test. The data used in this study are secondary data from the company's annual financial statements. The results of this study are that accounting conservatism has a positive effect on tax avoidance. Meanwhile, Corporate Governance and Sales Growth have a negative effect on Tax Avoidance.